PENGARUH MANAJEMEN ASET TERHADAP TINGKAT OPTIMALITAS ASET TETAP (TANAH DAN BANGUNAN) PEMERINTAH KOTA BAUBAU - , Jusmin ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to analyze the impact of asset management towards optimality of fixed assets (land and buildings) in the Local Government in Baubau Regency. By using purposive sampling method the number of research samples was takenas much as 48 respondents. The variables used are assets inventory, audit legal of assets assessment, as well as supervision and asset control. Based on the analysis result using Multiple Linear Regression test indicated that the asset inventory individually are proven have positive and significant influence toward optimality of fixed assets (land and buildings) that means consistent with the hypothesis, individually the legal audit of assets are not proved have positive and significant influence to optimization of fixed assets (land and buildings) that means not consistent with the hypothesis, an individual assessment of the assets are indicated are proved has positive influence to optimality of fixed assets (land and buildings) that means consistent with the hypothesis, the supervision and asset control is proved have positive and significant influence to optimization of fixed assets (land and buildings) that means consistent with the hypothesis. While the analysis results together /simultaneously indicated that all four variables, namely the asset inventory, audit legal of assets, assets assessment as well as supervision and assets control are proved to have significant and positive influence to optimality of fixed assets (land and buildings) this is proved by the value of F count > F-table.